UNUSUAL DELIVERY: NATURAL BIRTH OF A SCHISTOSOMA REFLEXUS DEFORMITY IN A MURRAH BUFFALO - Thompson, Emily (Ayden Journal of Agriculture and Allied Studies, 2024)
Schistosoma reflexus is an uncommon congenital disorder found primarily in ruminants, stemming from the inheritance of an autosomal recessive gene with variable penetrance during embryonic development. This disorder is typified by an exaggerated ventral curvature of the spine, malformations in the pelvis, and contorted body and chest structures, leading to the exposure of thoracic and abdominal viscera. The consequential dystocia emerges due to the vulnerability of abdominal organs in cattle and buffaloes. To facilitate the birthing of fully developed Schistosoma reflexus monstrosities, procedures such as fetotomy or caesarean section are imperative, while smaller monstrosities are occasionally expelled per-vaginally without obstetrical intervention. The worldwide prevalence of this disorder within bovine dystocia ranges between 0.01% and 1.3%. Recent research indicates that the Schistosoma reflexus syndrome may be attributed to hereditary anomalies in ruminants, affecting the intermediate mesoderm during the initial stages of postgastrulation embryogenesis. This article presents a comprehensive account of a dystocic event in a pregnant Murrah buffalo due to a Schistosoma reflexus monstrosity. The successful management of this case involved the application of Thygeson's fetotome for fetotomy. The case study not only delves into the diagnosis and treatment modalities employed but also highlights notable anatomical observations. In view of the aforementioned case, it is evident that prompt recognition and suitable obstetrical intervention are crucial in effectively managing dystocia attributed to Schistosoma reflexus.